Evaluating constraints and prospects of black soldier fly frass for sustainable Coelogyne pandurata acclimatization (Asian Journal of Agriculture, 2025)
Abstract. Kusuma R, Wulandari TM, Lariman, Samsurianto, Nugroho RA, Manurung H, Aryani R, Rudianto. 2025. Evaluating constraints and prospects of black soldier fly frass for sustainable Coelogyne pandurata acclimatization. Asian J Agric 9: 316-325. The black orchid (Coelogyne pandurata Lindl), a critically endangered species endemic to Borneo, faces significant threats from habitat destruction and over collection. In vitro propagation provides an effective conservation strategy; however, the acclimatization phase remains a major hurdle. This study assessed the potential of Black Soldier Fly Larvae (BSFL) frass as an organic amendment for the ex-vitro acclimatization of C. pandurata, in comparison with traditional substrates (husk charcoal, cocopeat, and fern roots), with and without supplemental fertilizer. Over 56 days, growth parameters including survival rate, plant height, leaf production, and shoot emergence were evaluated. While husk charcoal showed the highest height gain (3.23 ± 0.31 cm), cocopeat with 2 g L-1 of fertilizer resulted in superior leaf (3.47 ± 2.06) and shoot (2.49 ± 0.49) development. Despite its high nitrogen and micronutrient content, BSFL frass underperforms when used alone because of its poor structure and rapid nutrient release but may be beneficial as a supplement. These findings highlight the importance of the media types and nutrient balance in successful orchid acclimatization. This research not only supports sustainable conservation practices for C. pandurata but also promotes the upcycling of organic waste via BSFL frass, contributing to environmentally responsible horticultural applications.
Keywords: Acclimatization, black orchid, black soldier fly frass, conservation, plant tissue culture